1979
DOI: 10.1159/000137308
|View full text |Cite
|
Sign up to set email alerts
|

Dual Histamine Receptor Mechanism in Guinea-Pig Lung

Abstract: Isolated guinea-pig lung parenchymal strips (GPLS) relaxed in response to the selective histamine H2-receptor agonists, dimaprit and 4-methylhistamine (4-MeH), and to low doses of histamine (10–9 to 10–7 mol/l) and contracted in response to several spasmogens. The order of the relative activity of the spasmogens was 2-methylhistamine (2-MeH) > histamine > carbachol > 2-pyridylethylamine (2-PE). Dimaprit and 4-MeH also relaxed GPLS which were contracted by 2-MeH, 2-PE or carbach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Dissociation constant (pA2) values of 8.0-9.3 for mepyramine and 6.1-7.0 for cimetidine have been reported in different test preparations (Ottosson et al, 1988). Thus, the pA2 values found in the present study, 9.57 and 8.75 for mepyramine In some species, bronchodilatation is mediated via H2-receptors (Okpako et al, 1978;Chand & De Roth, 1979). In contrast, and Vincec et al (1984) have described a histamine-induced tracheal relaxation not affected by H2-antagonists and have suggested the existence of HIreceptor subtypes or a third histamine receptor in the trachea.…”
Section: Discussionsupporting
confidence: 64%
“…Dissociation constant (pA2) values of 8.0-9.3 for mepyramine and 6.1-7.0 for cimetidine have been reported in different test preparations (Ottosson et al, 1988). Thus, the pA2 values found in the present study, 9.57 and 8.75 for mepyramine In some species, bronchodilatation is mediated via H2-receptors (Okpako et al, 1978;Chand & De Roth, 1979). In contrast, and Vincec et al (1984) have described a histamine-induced tracheal relaxation not affected by H2-antagonists and have suggested the existence of HIreceptor subtypes or a third histamine receptor in the trachea.…”
Section: Discussionsupporting
confidence: 64%
“…Inasmuch as the guinea pig is highly sensitive to histamine (24,25) and easily subjected to anaphylaxis (26,27), we next used individual bronchial rings microdissected from sensitized guinea pigs and determined whether renin could be released in active form by anaphylactic mast cell degranulation, leading to ANG II formation and, thus, BC. Antigen challenge of bronchial rings excised from sensitized guinea pigs resulted in a smooth muscle contraction comparable in amplitude to that elicited by maximal depolarization with K ϩ (80 mM) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that activa tion of the H| receptors results in contraction of the guinea pig respiratory smooth muscles, while H2 re ceptor activation is accompanied by smooth muscle relaxation [Okpako et al, 1978;Drazen et al, 1979;Chand and de Roth, 1978;Harrison et al, 1984], It was shown that stobadine, a potent antiarrhythmic and cardioprotective drug [Stoic et al, 1983], and its racemate carbidine had pronounced antihistaminic effects on the guinea pig ileum, cat peripheral and central nervous system [Lukovic and Machova, 1984] and respiratory smooth muscles in vivo [Bauer and Buran, 1987;Buran et al, 1987],…”
Section: Introductionmentioning
confidence: 99%